2008
DOI: 10.1111/j.1469-185x.2008.00047.x
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the impact of climate variation on survival in vertebrate populations

Abstract: The impact of the ongoing rapid climate change on natural systems is a major issue for human societies. An important challenge for ecologists is to identify the climatic factors that drive temporal variation in demographic parameters, and, ultimately, the dynamics of natural populations. The analysis of long-term monitoring data at the individual scale is often the only available approach to estimate reliably demographic parameters of vertebrate populations. We review statistical procedures used in these analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
522
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(525 citation statements)
references
References 229 publications
(474 reference statements)
2
522
1
Order By: Relevance
“…An important consideration for understanding long-term population declines is that these declines can only be driven by covariates that also display a linear trend over the same time period [25]. However, the widespread decline in forest cover and habitat quality across all regions makes it difficult to conclusively demonstrate that wood thrush declines were driven by habitat degradation within any specific region.…”
Section: (B) Environmental Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…An important consideration for understanding long-term population declines is that these declines can only be driven by covariates that also display a linear trend over the same time period [25]. However, the widespread decline in forest cover and habitat quality across all regions makes it difficult to conclusively demonstrate that wood thrush declines were driven by habitat degradation within any specific region.…”
Section: (B) Environmental Covariatesmentioning
confidence: 99%
“…However, the widespread decline in forest cover and habitat quality across all regions makes it difficult to conclusively demonstrate that wood thrush declines were driven by habitat degradation within any specific region. Therefore, we followed Grosbois et al [25] and removed temporal trends from all covariates and used the detrended estimates as the annual covariates in our analysis. Thus, important covariates must account for a significant fraction of the variation in annual abundance after accounting for the linear decline of the covariate.…”
Section: (B) Environmental Covariatesmentioning
confidence: 99%
“…The 95% confidence interval (CI) of the slope parameters was used, as well as Akaike's information criterion corrected (AICc) for small sample size [28] for inference. We considered a contaminant's effect to be statistically supported when 0 was outside the 95% CI of the mean of the slope of the relationship [29]. A composite model was then constructed by combining all the covariates that were detected to have an effect on demographic parameters.…”
Section: Materials and Methods (A) Study Area And Speciesmentioning
confidence: 99%
“…This procedure allowed an analysis of deviance to estimate the proportion of deviance in the full CMR model explained by each covariate (a deviance R 2 ; Grosbois et al 2008) in isolation from the other indices that have been identified as important drivers of population dynamics. We compared the fit of the generic time-varying model and each environmental covariate model with respect to a constant model.…”
Section: Environmental Correlates Of Survival and Recapture Probabilitymentioning
confidence: 99%
“…We ask whether the CMR data provide support for declines in juvenile survival rates, declines in adult survival rates, or increased variability in survival rates. We also examine the ability of environmental indices to explain variation in estimated survival rates through an integrated CMR modeling approach (Lebreton et al 1992;Grosbois et al 2008). …”
Section: Introductionmentioning
confidence: 99%